A self-tunable dynamic vibration absorber: Parkinson's disease's tremor suppression - Teixeira, C. J. (2013)
An approach to Parkinson's Disease's (PD) tremor suppression based on a self-tunable Dynamic Vibration Absorber (DVA) was studied in this research, where two configurations, differed by a damping element, were addressed. The DVA was designed, mathematically modeled, simulated and experimentally validated when attached to a wood beam, coupled to a vibration exciter, which was used as an oscillating body. The control law for self-tuning was implemented and its effectiveness was investigated through experiments. Two types of external accelerations were used to test the system's performance. The first one was sinusoidal oscillations, where the input frequency could be varied; and the second a PD's waveform collected by sensors in patients and reproduced by a vibration exciter. The final configurations of the self-tunable DVA system was able to reduce oscillations in the order of 90% and 50%, respectively, for these tests.